2015
DOI: 10.1242/dev.116715
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of phospho-regulators of Wnt signaling inDrosophila

Abstract: Evolutionarily conserved intercellular signaling pathways regulate embryonic development and adult tissue homeostasis in metazoans. The precise control of the state and amplitude of signaling pathways is achieved in part through the kinase-and phosphatase-mediated reversible phosphorylation of proteins. In this study, we performed a genome-wide in vivo RNAi screen for kinases and phosphatases that regulate the Wnt pathway under physiological conditions in the Drosophila wing disc. Our analyses have identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 107 publications
(99 reference statements)
3
37
0
Order By: Relevance
“…However, this compound is known to inhibit other kinases, suggesting that repression of Wnt signalling may not be specific to LRRK2. This was a major concern since canonical Wnt signalling is regulated by a large number of kinases [60]. Thus, the experiment was repeated over a concentration gradient, to look for effects at concentrations closer to the reported IC50 for the compound, and in a second cell line, HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…However, this compound is known to inhibit other kinases, suggesting that repression of Wnt signalling may not be specific to LRRK2. This was a major concern since canonical Wnt signalling is regulated by a large number of kinases [60]. Thus, the experiment was repeated over a concentration gradient, to look for effects at concentrations closer to the reported IC50 for the compound, and in a second cell line, HEK293 cells.…”
Section: Resultsmentioning
confidence: 99%
“…There is a gap in understanding of how these two key signaling pathways interact in a normal context for proper organismal development. In a kinome and phosphatome RNA interference (RNAi) screen in the developing Drosophila larva, multiple components of the EGFR-Ras-MAPK signaling cascade were found to affect Wg signaling (Swarup et al, 2015). Here, we show that Dsor1 plays a crucial conserved function in mammalian cells and Drosophila in promoting Wg signaling.…”
Section: Introductionmentioning
confidence: 89%
“…Several kinases and phosphatases from the EGFR-Ras-MAPK pathway have been previously identified in an RNAi screen based on their ability to modulate Wg target gene expression (Swarup et al, 2015). We focused our attention on Dsor1, as it was the most terminal protein in the EGFR signaling cascade identified in the screen.…”
Section: Dsor1 Interacts With the Wg Pathway To Promote Target Gene Ementioning
confidence: 99%
“…Phenotypically, overexpression of dominant-negative Wnk, in vivo RNAi mediated knockdown of wnk in the wing, or loss of wnk function in mutant clones (patches of homozygous mutant wnk cells in a heterozygous background) cause lack of sensory bristles and margin defects in the adult wing (Sato and Shibuya, 2013; Serysheva et al, 2013). On the molecular level, staining of 3 rd instar wing imaginal discs showed that Sens and Dll expression are lost after RNAi-mediated knockdown of wnk (Serysheva et al, 2013; Swarup et al, 2015) and Sens is lost in a cell autonomous manner in wnk mutant clones (Fig. 5L) (Serysheva et al, 2013).…”
Section: Emerging Functions Of the Wnk Signaling Axis In Developmentmentioning
confidence: 99%
“…First, in a cell culture based screen, knockdown of wnk was found to reduce the level of Dsh phosphorylation (Serysheva et al, 2013). The second screen was an in vivo knockdown screen monitoring Wnt targets by immunohistochemistry (Swarup et al, 2015). Phenotypically, overexpression of dominant-negative Wnk, in vivo RNAi mediated knockdown of wnk in the wing, or loss of wnk function in mutant clones (patches of homozygous mutant wnk cells in a heterozygous background) cause lack of sensory bristles and margin defects in the adult wing (Sato and Shibuya, 2013; Serysheva et al, 2013).…”
Section: Emerging Functions Of the Wnk Signaling Axis In Developmentmentioning
confidence: 99%